2019
DOI: 10.1038/s41598-019-40434-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between Psychosocial Stress and Fecal Microbiota in Pregnant Women

Abstract: Maternal prenatal psychosocial stress is associated with altered child emotional and behavioral development. One potential underlying mechanism is that prenatal psychosocial stress affects child outcomes via the mother’s, and in turn the child’s, intestinal microbiota. This study investigates the first step of this mechanism: the relation between psychosocial stress and fecal microbiota in pregnant mothers. Mothers (N = 70) provided a late pregnancy stool sample and filled in questionnaires on general and preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 49 publications
2
56
0
2
Order By: Relevance
“…A stress-associated vaginal microbiome in female mice can be transmitted to the infant during birth, which in turn can impact the developing infant's health, metabolism, and stress response (Jašarevi c et al, 2015(Jašarevi c et al, , 2018. While the actual vertical transmission of stress-associated microbes has not yet been observed in humans, researchers have detected stress-associated microbial changes in the maternal human gut during pregnancy (Hechler et al, 2019). In addition, it has been shown that prenatal stress in pregnant monkeys alters the microbial composition of the infant gut (Bailey, Lubach, & Coe, 2004).…”
Section: Microbial Associations With Emotion and Social Behaviomentioning
confidence: 99%
“…A stress-associated vaginal microbiome in female mice can be transmitted to the infant during birth, which in turn can impact the developing infant's health, metabolism, and stress response (Jašarevi c et al, 2015(Jašarevi c et al, , 2018. While the actual vertical transmission of stress-associated microbes has not yet been observed in humans, researchers have detected stress-associated microbial changes in the maternal human gut during pregnancy (Hechler et al, 2019). In addition, it has been shown that prenatal stress in pregnant monkeys alters the microbial composition of the infant gut (Bailey, Lubach, & Coe, 2004).…”
Section: Microbial Associations With Emotion and Social Behaviomentioning
confidence: 99%
“…40 It was recently shown that there are associations between anxiety and the fecal microbial composition during pregnancy. 41 Between 1 and 10% of pregnant women take SSRI antidepressants, 40 further highlighting the relevance of a potential effect of SSRI medication during this period on the gut microbiota and its metabolic output.…”
Section: Introductionmentioning
confidence: 99%
“…Our correlation analysis showed that there was a positive correlation between white matter integrity and the relative abundance of Holdemania and Eubacterium. These bacteria are both known to be changed in abundances in other disorders: Holdemania is increased in individuals with MDD [67][68][69], and Eubacterium is decreased in children with ASD [70]. However, to our knowledge, this is the first study that found significant correlations between these bacteria and brain structural and functional changes.…”
Section: Discussionmentioning
confidence: 78%